2019
DOI: 10.1123/ijsnem.2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Body Composition Assessed Using DXA and Surface Anthropometry Show Good Agreement in Elite Rugby Union Athletes

Abstract: Rugby union athletes have divergent body composition based on the demands of their on-field playing position and ethnicity. With an established association between physique traits and positional requirements, body composition assessment is routinely undertaken. Surface anthropometry and dual-energy X-ray absorptiometry (DXA) are the most common assessment techniques used, often undertaken synchronously. This study aims to investigate the association between DXA and surface anthropometry when assessing longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…These findings support previous studies which demonstrated forwards as having different body composition [ 11 , 12 , 13 , 15 , 16 ] and anthropometric characteristics than backs, including greater strength and absolute power measures, but slower sprint performance and less aerobic fitness [ 6 , 7 , 10 , 33 ]. The characteristic differences between forwards and backs can be attributed to specific positional demands, in which being larger and stronger can assist forwards with winning line outs, scrumming with more force [ 34 ], gaining and retaining possession of the ball at break downs [ 6 ], and absorbing more collisions through tackles and ball carries [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings support previous studies which demonstrated forwards as having different body composition [ 11 , 12 , 13 , 15 , 16 ] and anthropometric characteristics than backs, including greater strength and absolute power measures, but slower sprint performance and less aerobic fitness [ 6 , 7 , 10 , 33 ]. The characteristic differences between forwards and backs can be attributed to specific positional demands, in which being larger and stronger can assist forwards with winning line outs, scrumming with more force [ 34 ], gaining and retaining possession of the ball at break downs [ 6 ], and absorbing more collisions through tackles and ball carries [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Studies within southern [ 6 , 11 , 12 , 13 ] and northern hemisphere [ 7 , 15 ] professional RU players demonstrated similar anthropometric, body composition, and fitness characteristic differences between forwards and backs, as seen in the current study. Interestingly, both forwards and backs within our study demonstrated greater height, body mass, lean mass, and fat mass, but possessed less bone mass and percent body fat compared to professional RU players observed in the northern hemisphere (United Kingdom) [ 15 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations